(untitled) (Journal of Universal Science Research, 2025)
Computational linguistics in English Language learning classroom revolutionizes the way students approach to learner autonomy in the classroom. The introduction and facilitation of the classroom with AI tools helps in modern English Language learning, fosters self-directed learning, critical thinking, and creativity among language learners through various pedagogical methods used by the teachers of the language. This paper focuses on a segment from the smorgasbord and uses visual verbal pedagogical methods that interface with computational linguistics to explore an experiential learning curve between computational linguistics and learner autonomy. The paper highlights the potential benefits and opportunities for language learning in the classroom and beyond. There are challenges as well, as autonomous learning is about developing a more self-self-engaging and self-paced learning style, therefore sometimes it proves to be hindrance in developing speaking and listening skills if only limited to learner- computer based interface. Therefore, the interjectory role of a teacher as a facilitator and in peer-to-peer learning modes cannot be ruled out completely. Hence, autonomous learning does not in any sense belittle the role of a teacher as a mediator and a facilitator in this article, rather it outlines the ways and methods to use them as better resources for sustainable and enhanced learning processes.